Urban livestock-keeping: Contributions to food and nutrition security - Lindahl, Johanna F.; Magnusson, Ulf; Grace, Delia (Elsevier, 2019)
When more and more people live in cities, there is increased need to produce food close to and within cities. The high value of livestock products and the increasing demand from the growing urban middle classes create a niche for urban livestock keeping, which contribute to the food security and the livelihoods of many different value chain actors. This chapter explores the different kinds of urban livestock keeping in low and middle-income countries and provides a view of the dynamics as well as the importance.